Effect of Chitosan Dispersion and Microparticles on Older Streptococcus mutans Biofilms - Erika R. H. Kawakita; Ana Carolina S. Ré; Maria Paula G. Peixoto; Maíra P. Ferreira; Antônio P. Ricomini-Filho; Osvaldo Freitas; Carolina P. Aires (Molecules, 2019)
(1) Background: The effectiveness of chitosan to improve the action of antimicrobial compounds against planktonic bacteria and young biofilms has been widely investigated in Dentistry, where the biofilm lifecycle is a determining factor for the success of antibacterial treatment. In the present study, mature Streptococcus mutans biofilms were treated with chitosan dispersion (CD) or chitosan microparticles (CM). (2) Methods: CD at 0.25% and 1% were characterized by texture analysis, while CD at 2% was spray-dried to form CM, which were characterized with respect to particle size distribution, zeta potential, and morphology. After determining the minimum inhibitory and bactericidal concentrations, S. mutans biofilms were grown on glass slides exposed 8×/day to 10% sucrose and 2×/day to CD or CM at 0.25% and 1%. Biofilm viability and acidogenicity were determined, using appropriate control groups for each experiment. (3) Results: CD had high viscosity and CM were spherical, with narrow size distribution and positive zeta potential. CM affected bacterial viability and acidogenicity in mature S. mutans biofilms more strongly than CD, especially at 1%. (4) Conclusions: Both chitosan forms exerted antimicrobial effect against mature S. mutans biofilms. CM at 1% can reduce bacterial viability and acidogenicity more effectively than CD at 1%, and thereby be more effective to control the growth of mature biofilms in vitro.